Efficacy of Endophytic Bacteria Pantoea dispersa Strain DSM 30073 on The Growth of Ipomoea reptans - Rahayu, Triastuti; Sidiq, Yasir; Anhari, Minhatul Ulya; Zulperi, Dzarifah (Bioeksperimen: Jurnal Penelitian Biologi, 2024)
Pantoea dispersa strain DSM 30073 is an endophytic bacterium isolated from the Ambon banana plant. From in vitro tests, this strain shows characteristics such as PGPB (Plant Growth Promoting Bacteria) and can support the growth of Cavendish banana plants, but its effect on Ipomoea reptans is unknown. The purpose of this study was to determine the efficacy of endophytic bacteria Pantoea dispersa strain DSM 30073 against the growth of Ipomoea reptans. The research design used was a one-factor Complete Randomized Design (CRD), namely inoculation frequency (P): control (P0), one-time inoculation (P1), and two-time inoculation (P2). The inoculum was confirmed to be pure by gram staining and cultured on NB medium with a 24-hour shake at room temperature. After 24 hours, the cells were harvested, and a suspension was made by adding Ringer's solution until it reached an OD600 nm of 0.8 – 1. Seeds were sterilized using 70 % alcohol followed by 1 % NaOCl for 1 minute each, then washed using sterile aquadest 3 times.  Sterile seeds were inoculated with an inoculum suspension for 30 minutes (P1). After inoculation, seeds are planted on a sterile soil medium. Repeated inoculation is carried out on the 11th day (P2). The growth of Ipomoea reptans is observed: plant height (cm), number of leaves (strands), leaf stretch (cm), wet weight of the plant (g), root length (cm), and number of roots (total). After 30 days, data on plant height 16.1 cm (control) – 17.4 cm (inoculation), wet weight of plants 1.1 g (control) – 1.4 g (inoculation 2 times), number of leaves 7 strands (control) – 8 strands (inoculation 2 times), and leaf stretch 10.2 cm – 10.9 cm (inoculation 2 times). Inoculation of Pantoea dispersa strain DSM 30073 had no effect on plant height growth, wet weight, leaf number, and leaf stretch but was significantly different in root parameters. It can be concluded that the Pantoea dispersa was not seen to support the growth of Ipomoea reptans significantly until 30 days after inoculation.